1998
DOI: 10.1021/jp9801020
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effect on Selective Tunneling Abstraction Reaction by H Atoms in Neopentane−Alkane Mixtures at 4−100 K

Abstract: When H atoms are produced by the photolysis of HI or the radiolysis of neo-C5H12 in the neo-C5H12−i-C4H10(2 mol %) mixtures above 40 K, the H atoms react selectively with the solute i-C4H10. The selective reaction is suppressed below 30 K. The reactions have been studied by electron spin resonance and electron spin echo measurements at 4−100 K. The drastic temperature effect on the reaction by H atoms suggests that the H atoms concerned are not hot atoms, but thermal atoms. The thermal H atoms react with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It is concluded that the local motions of the solute assist the tunnelling abstraction by H atoms. 283 In 1,2-dimethylcyclohexane irradiated at 77 K, the dimethyl-cyclohexene radical cation is formed by a cis^trans stereoselective H 2 detachment from the primary radical cation occurring only for the cis-isomer. 284 In MCH and in binary matrices MCH^isopentane at 6^77 K, the pulse radiolysis of CFCl 3 solutions leads to an ion pair CFCl 3 ÁÁÁ Cl À (l max 430 nm).…”
Section: Solidsmentioning
confidence: 99%
“…It is concluded that the local motions of the solute assist the tunnelling abstraction by H atoms. 283 In 1,2-dimethylcyclohexane irradiated at 77 K, the dimethyl-cyclohexene radical cation is formed by a cis^trans stereoselective H 2 detachment from the primary radical cation occurring only for the cis-isomer. 284 In MCH and in binary matrices MCH^isopentane at 6^77 K, the pulse radiolysis of CFCl 3 solutions leads to an ion pair CFCl 3 ÁÁÁ Cl À (l max 430 nm).…”
Section: Solidsmentioning
confidence: 99%